High-entropy alloy coating, nickel-based interface cone with high-entropy alloy coating and preparation method of nickel-based interface cone
By preparing high-entropy alloy coating on the surface of the nickel-based interface cone and performing heat treatment, the problem of insufficient heat resistance, corrosion resistance and thermal conductivity of the nickel-based interface cone in high temperature, high pressure and corrosive environments is solved, and a longer service life and lower cost are achieved.
Patent Information
- Application Number
- CN202411618503.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
When used in high temperature, high pressure and corrosive environments, the existing nickel-based interface cones have insufficient heat resistance, corrosion resistance and thermal conductivity, resulting in short service life and high cost.
High-entropy alloy coating is used, with specific components including tantalum, tungsten, nickel, iron, molybdenum, ruthenium, platinum, zirconium, boron and other elements. The coating is prepared on the surface of the nickel-based interface cone by magnetron sputtering, and heat treatment is carried out to improve the density and thermal conductivity of the coating.
It improves the hardness, wear resistance, toughness and corrosion resistance of the nickel-based interface cone, enhances its continuous working ability under high-temperature plasma bombardment, reduces the amount of impurities introduced, and saves the cost of plating production.
Smart Images

Figure CN119710555A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy alloys, and in particular relates to a high entropy alloy coating, a nickel-based interface cone with the high entropy alloy coating, and a preparation method thereof. Background Art
[0002] In modern analytical science, inductively coupled plasma mass spectrometer ICP-MS, as a high-precision element detection and analysis instrument, stands out among similar detection instruments with its advantages of high efficiency and accuracy, simultaneous analysis of multiple elements, isotope analysis, high sensitivity and low detection limit. It is an indispensable emerging trace analysis technology. In the entire system of this instrument, the interface part mostly uses an interface cone structure to connect the ICP ion source with the mass spectrometer, which ensures the effective transmission of ions while maintaining the consistency and integrity of the ions. It cleverly combines the high-temperature ionization characteristics of inductively coupled plasma and the rapid scanning and sensitive performance of mass spectrometry, and is an important and key component of the ICP-MS instrument. The transmission characteristics of the interface cone directly affect the analytical performance of the instrument. Since the interface cone needs to face a high-temperature and high-speed ion source, it needs to withstand high temperature, high pressure and corrosive environment during work, so it puts forward high requirements on the heat resistance, corrosion resistance and thermal conductivity of the interface cone material. It is particularly important to produce and apply high-quality nickel-based interface cones to ensure the sensitivity, stability and service life of the instrument.
[0003] At present, the main method to improve the performance of nickel-based interface cones is to prepare oxide ceramic coatings such as aluminum oxide and zirconium oxide or platinum group metal coatings on the surface of nickel-based interface cones. Among them, the oxide ceramic coating preferentially corrodes the oxide coating during use, protecting the nickel-based interface cone from corrosion, thereby extending its service life. However, the thermal conductivity of ceramic materials is low, which affects the heat dissipation of nickel-based interface cones, and oxide ceramics are not resistant to acid corrosion, so their use scenarios are limited and their service life is limited. Although platinum group metal coatings have good thermal conductivity and corrosion resistance, their use cost is high, which greatly increases the cost of a single test. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a high entropy alloy coating, a nickel-based interface cone with a high entropy alloy coating, and a preparation method thereof. The present invention specifically comprises the following steps:
[0005] A high entropy alloy coating, wherein the high entropy alloy comprises, by mass percentage:
[0006] Tantalum: 15-20%;
[0007] Tungsten: 10-15%;
[0008] Nickel: 14-20%;
[0009] Iron: 3-8%;
[0010] Molybdenum: 9-13%;
[0011] The balance is one or more of ruthenium, platinum, zirconium and boron;
[0012] The grain size of the high entropy alloy coating is ≤1 μm and the density is ≥99.8%.
[0013] Furthermore, the thickness of the high entropy alloy coating is 0.1-0.6 μm; and / or the surface roughness is less than 0.5 μm.
[0014] Furthermore, the thermal conductivity of the high entropy alloy coating is ≥140 W / (m·K).
[0015] A nickel-based interface cone with the high-entropy alloy coating.
[0016] Furthermore, the nickel-based interface cone with a high-entropy alloy coating can work continuously for ≥80 hours under 4000-8000K high-temperature plasma bombardment.
[0017] Furthermore, the high entropy alloy coating on the surface of the nickel-based interface cone can work in an environment of pH ≤ 3 or pH ≥ 9, and the corroded products will not fall off after corrosion in a strong acid or strong alkali environment, and the amount of impurities introduced is ≤ 0.5 ppm.
[0018] A method for preparing a nickel-based interface cone with a high entropy alloy coating comprises the following steps:
[0019] S1, sputtering coating: in an inert gas atmosphere, using the high entropy alloy as a target, a high entropy alloy coating is prepared on the surface of a nickel-based interface cone by magnetron sputtering;
[0020] S2, coating heat treatment: subjecting the nickel-based interface cone with a high entropy alloy coating sputtered on its surface to vacuum heat treatment, followed by cooling to obtain the nickel-based interface cone with a high entropy alloy coating.
[0021] Further, step S1: the inert gas is argon, and the pressure of the argon atmosphere is (2-5)×10 -1 Pa; and / or, the power of the magnetron sputtering is 50-80W and the time is 5-10min; and / or, the magnetron sputtering power supply adopts a DC power supply.
[0022] Further, in step S2: the vacuum degree of the vacuum heat treatment is ≤2×10 -4 Pa, the holding temperature is 300-500℃, and the holding time is 0.5-3h.
[0023] Furthermore, before the sputtering coating step S1, the method further includes: S0 pre-sputtering: using a baffle to cover the nickel-based interface cone, pre-sputtering the target material, and removing the target material stress and the surface oxide layer.
[0024] Furthermore, the pre-sputtering in step S0 is performed at a pressure of (1-3)×10 -1 The pre-sputtering is carried out in an argon atmosphere of 0.06 Pa, and / or the pre-sputtering power is 30-150 W, and the pre-sputtering time is 3-15 min.
[0025] Furthermore, before sputtering coating, the method further includes: using an acidic washing solution with a mass ratio of hydrochloric acid to sulfuric acid of 1:(0.8-1.2) and a total mass concentration of ≤10% to immerse and clean the nickel-based interface cone, wherein the immersion and cleaning time is 5-15 minutes, and the immersion and cleaning are followed by drying for 10-30 minutes, wherein the surface roughness of the nickel-based interface cone after immersion and cleaning is 1-5 μm; and / or, before sputtering coating, the method further includes: heating the nickel-based interface cone to 100-250° C. and keeping the temperature for 5-15 minutes.
[0026] Beneficial effects of the present invention:
[0027] (1) The core feature of high entropy alloys is their high mixing entropy, which helps the alloys form a simple solid solution structure rather than a complex intermetallic compound during solidification. In this solid solution structure, the distribution of various alloying elements in the lattice is more uniform, reducing the phenomenon of element segregation and grain boundary enrichment. The present invention adds 15-20% tantalum and 10-15% tungsten to the high entropy alloy coating, which can increase the hardness and wear resistance of the coating, and also help to improve the density of the coating. Adding 14-20% nickel helps to form a stable solid solution structure, and at the same time can improve the toughness and corrosion resistance of the coating. Adding 3-8% iron can further increase the strength and hardness of the coating, and the interaction between iron and other elements also helps to form a more dense microstructure. Adding 9-13% molybdenum can significantly improve the high temperature resistance and corrosion resistance of the coating, and also help to improve the density of the coating. Moreover, the tantalum, nickel, molybdenum and other elements in the high entropy alloy coating of the present invention can form a dense oxide film or passivation layer outside the coating, so that the coating has good corrosion resistance. In addition, the addition of a certain amount of one or more of ruthenium, platinum, zirconium, and boron can further adjust the properties of the coating. For example, ruthenium and platinum have excellent corrosion resistance and high temperature stability; the addition of zirconium can improve the strength and hardness of the coating; the addition of boron helps to form an amorphous structure, further improving the density and wear resistance of the coating. Moreover, due to the differences in the atomic size and properties of various elements such as tantalum, tungsten, nickel, ruthenium, iron, zirconium, molybdenum, platinum, and boron, their distribution in the lattice will cause lattice distortion, which not only helps to improve the strength and hardness of the coating, but also helps to promote the densification of the coating. The high entropy alloy coating of the present invention has a grain size of ≤1μm, a density of ≥99.8%, and a thermal conductivity of ≥140W / (m·K).
[0028] (2) Before the magnetron sputtering surface is used to prepare the high entropy alloy coating, the target material is pre-sputtered to remove the oxide layer and stress layer on the target material surface. The oxide layer contains more oxygen atoms, which will cause the coating to produce more atomic-level point defects and line defects after sputtering. Point defects and line defects will cause the atoms around the defects to have greater distortion energy, which will reduce the vibration conduction efficiency, that is, affect the thermal conductivity of the coating. Similarly, the target material stress layer is prone to abnormal discharge or large particles falling onto the coating surface during the sputtering process, affecting the uniformity and performance of the target material. Before magnetron sputtering, the present invention also uses a special acidic lotion to clean the surface of the nickel-based interface cone, which can corrode the surface of the nickel-based interface cone and increase its surface roughness to 1-5μm, so that the bonding strength between the subsequent coating and the nickel-based interface cone substrate is increased by 50%.
[0029] (3) The present invention adopts a magnetron sputtering method to prepare a coating on the surface of a nickel-based interface cone, and combines the coating composition and the characteristics of the nickel-based interface cone to improve the magnetron sputtering process, which can significantly enhance the adhesion between the high entropy alloy coating and the nickel-based interface cone, improve the density and strength of the coating, reduce the surface roughness, prevent the coating from falling off due to impact, high temperature, corrosion, etc. in subsequent use, and improve the performance of the nickel-based interface cone with a high entropy alloy coating. In addition, the present invention also heat treats the coating after magnetron sputtering, and designs the heat treatment temperature and time. The appropriate heat treatment temperature and time can make the coating sputtered on the surface of the nickel-based interface cone fully atomically diffuse, reduce various coating defects to ensure the performance of the coating. The nickel-based interface cone with a high entropy alloy coating prepared by the present invention has a continuous working time of ≥80h under 4000-8000K high temperature plasma bombardment, and will not corrode and fall off in a working environment with pH≤3 or pH≥9, and the amount of impurities introduced is ≤0.5ppm. In addition, the nickel-based interface cone with a high entropy alloy coating of the present invention can save more than 20%-30% of the production cost of the coating compared to the nickel-based interface cone with a platinum group metal coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A partially enlarged schematic diagram of a nickel-based interface cone with a high entropy alloy coating prepared in the present invention. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments shown below do not limit the invention content described in the claims. In addition, the entire contents of the structures represented by the following embodiments are not limited to those necessary for the solutions of the invention described in the claims.
[0032] A high entropy alloy coating, wherein the high entropy alloy comprises, by mass percentage, 15-20% tantalum, 10-15% tungsten, 14-20% nickel, 3-8% iron, 9-13% molybdenum, and the remainder is one or more of ruthenium, platinum, zirconium, and boron; the high entropy alloy coating has a grain size of ≤1 μm, a density of ≥99.8%, a thickness of 0.1-0.6 μm, a surface roughness of <0.5 μm, and a thermal conductivity of ≥140 W / (m·K).
[0033] refer to Figure 1 A nickel-based interface cone with the high-entropy alloy coating (including a high-entropy alloy coating 1 and a nickel-based interface cone 2) has a continuous working time of ≥80h under 4000-8000K high-temperature plasma bombardment, will not corrode or fall off in a working environment of pH ≤3 or pH ≥9, and the amount of impurities introduced is ≤0.5ppm.
[0034] A method for preparing a nickel-based interface cone with a high entropy alloy coating comprises the following steps:
[0035] Pretreatment of nickel-based interface cones: Use an acidic cleaning solution with a mass ratio of hydrochloric acid to sulfuric acid of 1:(0.8-1.2) and a total mass concentration of ≤10% to soak and clean the nickel-based interface cones. The soaking and cleaning time is 5-15 minutes, and then drying for 10-30 minutes. Place the treated nickel-based interface cones on the substrate stage of a magnetron sputtering device;
[0036] S0, pre-sputtering: close the sputtering baffle so that it completely covers the top of the interface cone, and the vacuum degree is ≤2×10 -4 Pa, open the vent valve and fill with argon to 2×10 -1 Pa, close the vent valve, and wait until the vacuum degree reaches ≤2×10 -4 Pa, open the vent valve and flow meter, control the argon filling rate to 20-60sccm, and adjust the pressure to maintain at 1×10 -1 Pa-3×10 -1 Pa, turn on the magnetron sputtering power supply, slowly increase the current, adjust the power to 30-150W for pre-sputtering, and the pre-sputtering time is 3-15min;
[0037] S1, sputtering coating: After the pre-sputtering is completed, the baffle is opened, the substrate stage is heated, the nickel-based interface cone is heated to 100-250°C, and the temperature is kept for 5-15 minutes, the argon filling rate is controlled to be 20-40 sccm, and the pressure is adjusted to maintain at (2-5)×10 - 1Pa, using the high entropy alloy as a target material, preparing a high entropy alloy coating on the surface of a nickel-based interface cone by magnetron sputtering; the magnetron sputtering uses direct current as a power source, controls the magnetron sputtering power to be 50-80W, and the time is 5-10min; the composition of the high entropy alloy target material is consistent with the high entropy alloy coating, the purity of the target material is ≥99.99%, and the grain size is ≤10μm;
[0038] S2, coating heat treatment: turn off the magnetron sputtering power supply, close the exhaust valve, stop the argon filling, and wait until the vacuum degree reaches ≤2×10 -4 Pa, heating the substrate stage for heat treatment, wherein the heat treatment is carried out at a holding temperature of 300-500°C and a holding time of 0.5-3h, and then cooling with the furnace for 5-8h to obtain the nickel-based interface cone with a high entropy alloy coating.
[0039] Example 1
[0040] A method for preparing a nickel-based interface cone with a high-entropy alloy coating comprises taking a high-entropy alloy target as a raw material and preparing the high-entropy alloy coating on the outside of the nickel-based interface cone by a magnetron sputtering method.
[0041] The purity of the high entropy alloy target used in this embodiment is ≥99.99%, the grain size is ≤10μm, and the composition and mass content include: tantalum 16%; tungsten 11%; nickel 14%; iron 5%; molybdenum 10%; the remainder is one or more of ruthenium, platinum, zirconium, and boron.
[0042] The preparation method of this embodiment comprises the following steps:
[0043] Pretreatment of nickel-based interface cones: Use an acidic cleaning solution with a mass ratio of hydrochloric acid to sulfuric acid of 1:1 and a total mass concentration of 10% to soak and clean the nickel-based interface cones. The soaking and cleaning time is 10 minutes, and then dry for 20 minutes. Place the treated nickel-based interface cones on the substrate stage of the magnetron sputtering device;
[0044] S0, pre-sputtering: close the sputtering baffle so that it completely covers the top of the interface cone, and the vacuum degree is ≤2×10 -4 Pa, open the vent valve and fill with argon to 2×10 -1 Pa, close the vent valve, and wait until the vacuum degree reaches ≤2×10 -4 Pa, open the vent valve and flow meter, control the argon filling rate to 30 sccm, and adjust the pressure to maintain at 2×10 -1 Pa, turn on the magnetron sputtering power supply, slowly increase the current, adjust the power to 110W for pre-sputtering, and the pre-sputtering time is 8min;
[0045] S1, sputtering coating: After the pre-sputtering, the baffle was opened, the substrate stage was heated, the nickel-based interface cone was heated to 180°C, and kept warm for 9 minutes, the argon filling rate was controlled to 33 sccm, and the pressure was adjusted to maintain at 3×10 -1 Pa, using the high entropy alloy as a target material, preparing a high entropy alloy coating on the surface of a nickel-based interface cone by magnetron sputtering; the magnetron sputtering uses direct current as a power source, controls the magnetron sputtering power to be 65 W, and the time is 8 minutes;
[0046] S2, coating heat treatment: turn off the magnetron sputtering power supply, close the exhaust valve, stop the argon filling, and wait until the vacuum degree reaches ≤2×10 -4 Pa, heating the substrate stage for heat treatment, the heat treatment temperature is 400 ° C, the heat treatment time is 2 hours, and then cooling with the furnace for 6 hours to obtain the nickel-based interface cone with high entropy alloy coating.
[0047] After testing, the grain size of the high entropy alloy coating prepared in this embodiment is generally ≤1μm, the density is more than 99.9%, the thickness is 0.5μm, the surface roughness is 0.4μm, and the thermal conductivity is 165W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment can work continuously for 96 hours under 4000-8000K high temperature plasma bombardment, and no corrosion products will fall off in a working environment of pH≤3 or pH≥9, and the amount of impurities introduced is less than 0.5pm.
[0048] Example 2
[0049] A method for preparing a nickel-based interface cone with a high-entropy alloy coating comprises taking a high-entropy alloy target as a raw material and preparing the high-entropy alloy coating on the outside of the nickel-based interface cone by a magnetron sputtering method.
[0050] The purity of the high entropy alloy target used in this embodiment is ≥99.99%, the grain size is ≤10μm, and the composition and mass content include: 20% tantalum; 10% tungsten; 17% nickel; 3% iron; 9% molybdenum; the remainder is one or more of ruthenium, platinum, zirconium, and boron.
[0051] The preparation method of this embodiment comprises the following steps:
[0052] Pretreatment of nickel-based interface cones: Use an acidic cleaning solution with a mass ratio of hydrochloric acid to sulfuric acid of 1:0.8 and a total mass concentration of 9% to soak and clean the nickel-based interface cones for 5 minutes, then dry for 25 minutes, and place the treated nickel-based interface cones on the substrate stage of a magnetron sputtering device;
[0053] S0, pre-sputtering: close the sputtering baffle so that it completely covers the top of the interface cone, and the vacuum degree is ≤2×10 -4 Pa, open the vent valve and fill with argon to 2×10 -1Pa, close the vent valve, and wait until the vacuum degree reaches ≤2×10 -4 Pa, open the vent valve and flow meter, control the argon filling rate to 40 sccm, and adjust the pressure to maintain at 2×10 -1 Pa, turn on the magnetron sputtering power supply, slowly increase the current, adjust the power to 80W for pre-sputtering, and the pre-sputtering time is 5min;
[0054] S1, sputtering coating: After the pre-sputtering, open the baffle, heat the substrate stage, heat the nickel-based interface cone to 150°C, and keep it warm for 7 minutes. Control the argon filling rate to 40 sccm and adjust the pressure to maintain at 3×10 -1 Pa, using the high entropy alloy as a target material, preparing a high entropy alloy coating on the surface of a nickel-based interface cone by magnetron sputtering; the magnetron sputtering uses direct current as a power source, controls the magnetron sputtering power to be 70 W, and the time is 10 min;
[0055] S2, coating heat treatment: turn off the magnetron sputtering power supply, close the exhaust valve, stop the argon filling, and wait until the vacuum degree reaches ≤2×10 -4 Pa, heating the substrate stage for heat treatment, the heat treatment temperature is 300 ° C, the heat treatment time is 0.5h, and then cooling with the furnace for 7h to obtain the nickel-based interface cone with high entropy alloy coating.
[0056] After testing, the grain size of the high entropy alloy coating prepared in this embodiment is ≤0.9μm, the density is more than 99.8%, the thickness is 0.3μm, the surface roughness is 0.2μm, and the thermal conductivity is 140W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment can work continuously for 86 hours under 4000-8000K high temperature plasma bombardment, and no corrosion products will fall off in a working environment of pH≤3 or pH≥9, and the amount of impurities introduced is ≤0.5ppm.
[0057] Example 3
[0058] A method for preparing a nickel-based interface cone with a high-entropy alloy coating comprises taking a high-entropy alloy target as a raw material and preparing the high-entropy alloy coating on the outside of the nickel-based interface cone by a magnetron sputtering method.
[0059] The purity of the high entropy alloy target used in this embodiment is ≥99.99%, the grain size is ≤10μm, and the composition and mass content include: tantalum 17%; tungsten 15%; nickel 17%; iron 5%; molybdenum 13%; the remainder is one or more of ruthenium, platinum, zirconium, and boron.
[0060] The preparation method of this embodiment comprises the following steps:
[0061] Pretreatment of nickel-based interface cones: Use an acidic cleaning solution with a mass ratio of hydrochloric acid to sulfuric acid of 1:1.2 and a total mass concentration of 8% to soak and clean the nickel-based interface cones for 15 minutes, then dry for 30 minutes, and place the treated nickel-based interface cones on the substrate stage of a magnetron sputtering device;
[0062] S0, pre-sputtering: close the sputtering baffle so that it completely covers the top of the interface cone, and the vacuum degree is ≤2×10 -4 Pa, open the vent valve and fill with argon to 2×10 -1 Pa, close the vent valve, and wait until the vacuum degree reaches ≤2×10 -4 Pa, open the vent valve and flow meter, control the argon filling rate to 23sccm, and adjust the pressure to maintain at 2×10 -1 Pa, turn on the magnetron sputtering power supply, slowly increase the current, adjust the power to 65W for pre-sputtering, and the pre-sputtering time is 6min;
[0063] S1, sputtering coating: After the pre-sputtering, the baffle was opened, the substrate stage was heated, the nickel-based interface cone was heated to 150°C, and kept warm for 8 min, the argon filling rate was controlled to 25 sccm, and the pressure was adjusted to maintain at 3×10 -1 Pa, using the high entropy alloy as a target material, preparing a high entropy alloy coating on the surface of a nickel-based interface cone by magnetron sputtering; the magnetron sputtering uses direct current as a power source, controls the magnetron sputtering power to be 55 W, and the time is 12 minutes;
[0064] S2, coating heat treatment: turn off the magnetron sputtering power supply, close the exhaust valve, stop the argon filling, and wait until the vacuum degree reaches ≤2×10 -4 Pa, heating the substrate stage for heat treatment, the heat treatment temperature is 500 ° C, the heat treatment time is 3 hours, and then cooling with the furnace for 7 hours to obtain the nickel-based interface cone with high entropy alloy coating.
[0065] After testing, the grain size of the high entropy alloy coating prepared in this embodiment is ≤0.8μm, the density is more than 99.9%, the thickness is 0.5μm, the surface roughness is 0.3μm, and the thermal conductivity is 170W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment can work continuously for 85h under 4000-8000K high temperature plasma bombardment, and no corrosion products will fall off in a working environment of pH≤3 or pH≥9, and the amount of impurities introduced is ≤0.5ppm.
[0066] Example 4
[0067] A method for preparing a nickel-based interface cone with a high-entropy alloy coating comprises taking a high-entropy alloy target as a raw material and preparing the high-entropy alloy coating on the outside of the nickel-based interface cone by a magnetron sputtering method.
[0068] The purity of the high entropy alloy target used in this embodiment is ≥99.99%, the grain size is ≤10μm, and the composition and mass content include: tantalum 18%; tungsten 12%; nickel 16%; iron 8%; molybdenum 11%; the remainder is one or more of ruthenium, platinum, zirconium, and boron.
[0069] The preparation method of this embodiment comprises the following steps:
[0070] Pretreatment of nickel-based interface cones: Use an acidic cleaning solution with a mass ratio of hydrochloric acid to sulfuric acid of 1:1 and a total mass concentration of 8% to soak and clean the nickel-based interface cones for 12 minutes, then dry for 15 minutes, and place the treated nickel-based interface cones on the substrate stage of a magnetron sputtering device;
[0071] S0, pre-sputtering: close the sputtering baffle so that it completely covers the top of the interface cone, and the vacuum degree is ≤2×10 -4 Pa, open the vent valve and fill with argon to 2×10 -1 Pa, close the vent valve, and wait until the vacuum degree reaches ≤2×10 -4 Pa, open the vent valve and flow meter, control the argon filling rate to 55 sccm, and adjust the pressure to maintain at 2×10 -1 Pa, turn on the magnetron sputtering power supply, slowly increase the current, adjust the power to 95W for pre-sputtering, and the pre-sputtering time is 10min;
[0072] S1, sputtering coating: After the pre-sputtering, the baffle was opened, the substrate stage was heated, the nickel-based interface cone was heated to 140°C, and kept warm for 9 minutes, the argon filling rate was controlled to 30 sccm, and the pressure was adjusted to maintain at 3×10 -1 Pa, using the high entropy alloy as a target material, preparing a high entropy alloy coating on the surface of a nickel-based interface cone by magnetron sputtering; the magnetron sputtering uses direct current as a power source, controls the magnetron sputtering power to be 80 W, and the time is 10 min;
[0073] S2, coating heat treatment: turn off the magnetron sputtering power supply, close the exhaust valve, stop the argon filling, and wait until the vacuum degree reaches ≤2×10 -4 Pa, heating the substrate stage for heat treatment, the heat treatment temperature is 450 ° C, the heat treatment time is 1.5 hours, and then the furnace is cooled for 6 hours to obtain the nickel-based interface cone with high entropy alloy coating.
[0074] After testing, the grain size of the high entropy alloy coating prepared in this embodiment is ≤0.5μm, the density is more than 99.9%, the thickness is 0.2μm, the surface roughness is 0.3μm, and the thermal conductivity is 153W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment can work continuously for 85h under 4000-8000K high temperature plasma bombardment, and no corrosion products will fall off in a working environment of pH≤3 or pH≥9, and the amount of impurities introduced is ≤0.5ppm.
[0075] Comparative Example 1
[0076] The difference between this comparative example and Example 1 is that the mass content of tantalum in the high entropy alloy target used is 12%, and the mass content of tungsten is 8%, and other conditions are the same.
[0077] After testing, the grain size of the high entropy alloy coating prepared in this comparative example is ≤1μm, the density is 90.2%, the thickness is 0.4μm, the surface roughness is 0.4μm, and the thermal conductivity is 125W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this comparative example has a continuous working time of 55h under 4000-8000K high-temperature plasma bombardment, no corrosion products will fall off in a working environment of pH≤3 or pH≥9, and the amount of impurities introduced is ≤0.5ppm. This comparative example shows that if the content of tantalum and tungsten in the high entropy alloy coating is too low, the continuous working time of the nickel-based interface cone with a high entropy alloy coating will be reduced, and the thermal conductivity will be reduced.
[0078] Comparative Example 2
[0079] The difference between this comparative example and Example 1 is that the mass content of tantalum in the high entropy alloy target used is 25%, and the mass content of tungsten is 20%, and other conditions are the same.
[0080] After testing, the grain size of the high entropy alloy coating prepared in this embodiment is generally ≤1μm, the density is more than 95.7%, the thickness is 0.4μm, the surface roughness is 0.4μm, and the thermal conductivity is 143W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment has a continuous working time of 76h under 4000-8000K high-temperature plasma bombardment, and corrosion products will fall off in a working environment of pH≤3 or pH≥9. This comparative example shows that if the content of tantalum and tungsten in the high entropy alloy coating is too high, the continuous working time of the nickel-based interface cone with a high entropy alloy coating will be reduced, and the acid and alkali corrosion resistance will be reduced.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 1 is that the mass content of nickel in the high entropy alloy target used is 12%, and the mass content of molybdenum is 8%, and other conditions are the same.
[0083] After testing, the high entropy alloy coating prepared in this comparative example has a grain size of ≤1μm, a density of 99.3%, a thickness of 0.4μm, a surface roughness of 0.4μm, and a thermal conductivity of 132W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this comparative example has a continuous working time of 72h under 4000-8000K high-temperature plasma bombardment, and there is a problem of corrosion products falling off in a working environment of pH≤3 or pH≥9. This comparative example shows that if the content of nickel and molybdenum in the high entropy alloy coating is too high, the continuous working time of the nickel-based interface cone with a high entropy alloy coating will be reduced, and the acid and alkali corrosion resistance and thermal conductivity will be reduced.
[0084] Comparative Example 4
[0085] The difference between this comparative example and Example 1 is that the mass content of nickel in the high entropy alloy target used is 23%, and the mass content of molybdenum is 15%, and other conditions are the same.
[0086] After testing, the grain size of the high entropy alloy coating prepared in this comparative example is ≤1μm, the density is 95.6%, the thickness is 0.4μm, the surface roughness is 0.4μm, and the thermal conductivity is 140W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this comparative example has a continuous working time of 40h under 4000-8000K high-temperature plasma bombardment, no corrosion products will fall off in a working environment of pH≤3 or pH≥9, and the amount of impurities introduced is ≤0.5ppm. This comparative example shows that if the content of nickel and molybdenum in the high entropy alloy coating is too high, the continuous working time of the nickel-based interface cone with a high entropy alloy coating will be reduced, and the acid and alkali corrosion resistance will be reduced.
[0087] Comparative Example 5
[0088] The difference between this comparative example and Example 1 is that the mass content of iron in the high entropy alloy target used is 1%, and other conditions are the same.
[0089] After testing, the grain size of the high entropy alloy coating prepared in this comparative example is ≤1μm, the density is 98.9%, the thickness is 0.4μm, the surface roughness is 0.6μm, and the thermal conductivity is 132W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this comparative example has a continuous working time of 72h under 4000-8000K high-temperature plasma bombardment, no corrosion products will fall off in a working environment of pH≤3 or pH≥9, and the amount of impurities introduced is ≤0.5ppm. This comparative example shows that if the iron content in the high entropy alloy coating is too low, the continuous working time of the nickel-based interface cone with a high entropy alloy coating will be reduced, and the acid and alkali corrosion resistance and thermal conductivity will be reduced.
[0090] Comparative Example 6
[0091] The difference between this comparative example and Example 1 is that the mass content of iron in the high entropy alloy target used is 10%, and other conditions are the same.
[0092] After testing, the grain size of the high entropy alloy coating prepared in this comparative example is ≤1μm, the density is 99.8%, the thickness is 0.4μm, the surface roughness is 0.4μm, and the thermal conductivity is 141W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this comparative example has a continuous working time of 52h under 4000-8000K high-temperature plasma bombardment, and there is a problem of corrosion products falling off in a working environment of pH≤3 or pH≥9. This comparative example shows that if the iron content in the high entropy alloy coating is too high, the continuous working time of the nickel-based interface cone with a high entropy alloy coating will be reduced, and the acid and alkali corrosion resistance will be reduced.
[0093] Comparative Example 7
[0094] The difference between this comparative example and Example 1 is that the cleaning time of the nickel-based interface cone surface is 2 minutes, and the surface roughness after cleaning is 0.8 μm, and other conditions are the same.
[0095] After testing, the high entropy alloy coating prepared in this embodiment has a grain size of ≤1μm, a density of more than 99.9%, a thickness of 0.4μm, a surface roughness of 0.5μm, and a thermal conductivity of 143W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment has a continuous working time of 52h under 4000-8000K high-temperature plasma bombardment, and corrosion products fall off in a working environment of pH≤3 or pH≥9. This comparative example shows that if the cleaning time of the nickel-based interface cone is too short before coating, the surface roughness of the nickel-based interface cone before coating will decrease, which will further reduce the bonding force between the high entropy alloy coating and the surface of the nickel-based interface cone, which will further reduce the continuous working time of the coated nickel-based interface cone and reduce the acid and alkali corrosion resistance.
[0096] Comparative Example 8
[0097] The difference between this comparative example and Example 1 is that no pre-sputtering treatment is performed, and other conditions are the same.
[0098] After testing, the high entropy alloy coating prepared in this embodiment has a grain size of ≤3μm, a density of 98.6%, a thickness of 0.4μm, a surface roughness of 1.3μm, and a thermal conductivity of 120W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment can work continuously for 48 hours under 4000-8000K high-temperature plasma bombardment, and corrosion products will fall off in a working environment with pH≤3 or pH≥9. This comparative example shows that if the magnetron sputtering target is not pre-sputtered, the impurity content in the coating alloy will be high, which will cause the thermal conductivity of the coating to decrease, and the continuous working time of the nickel-based interface cone with the coating will be reduced, and the acid and alkali corrosion resistance will be reduced.
[0099] Comparative Example 9
[0100] The difference between this comparative example and Example 1 is that the power of magnetron sputtering is 40 W, the sputtering time is 15 min, and other conditions are the same.
[0101] After testing, the high entropy alloy coating prepared in this embodiment has a grain size of ≤4μm, a density of 97.3%, a thickness of 0.1μm, a surface roughness of 1.1μm, and a thermal conductivity of 127W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment has a continuous working time of 62h under 4000-8000K high temperature plasma bombardment and corrosion products will fall off in a working environment of pH≤3 or pH≥9. This comparative example shows that if the power of the magnetron sputtering step is too low and the time is too long, the continuous working time of the nickel-based interface cone with a coating will be reduced, and the acid and alkali corrosion resistance and thermal conductivity will be reduced.
[0102] Comparative Example 10
[0103] The difference between this comparative example and Example 1 is that the power of magnetron sputtering is 100 W, the sputtering time is 3 min, and other conditions are the same.
[0104] After testing, the high entropy alloy coating prepared in this embodiment has a grain size of ≤4μm, a density of 98.5%, a thickness of 0.12mm, a surface roughness of 0.7μm, and a thermal conductivity of 133W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment has a continuous working time of 47h under 4000-8000K high-temperature plasma bombardment, no corrosion products will fall off in a working environment of pH≤3 or pH≥9, and the amount of impurities introduced is ≤0.5ppm. This comparative example shows that if the power of the magnetron sputtering step is too high and the time is too short, the continuous working time of the nickel-based interface cone with a coating will be reduced, and the thermal conductivity will be reduced.
[0105] Comparative Example 11
[0106] The difference between this comparative example and Example 1 is that no coating heat treatment is performed, and other conditions are the same.
[0107] After testing, the high entropy alloy coating prepared in this comparative example is not crystallized, has a density of less than 95.6%, a thickness of 0.4 μm, a surface roughness of 1.2 μm, and a thermal conductivity of 121 W / (m·K). The nickel-based interface cone with a high entropy alloy coating prepared in this embodiment has a continuous working time of 32 hours under 4000-8000K high-temperature plasma bombardment, and corrosion products fall off in a working environment of pH ≤ 3 or pH ≥ 9. This comparative example shows that the continuous working time of the nickel-based interface cone without a coating is low, and the acid and alkali corrosion resistance and thermal conductivity are poor.
[0108] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high entropy alloy coating, characterized in that: The high entropy alloy comprises, by mass percentage: Tantalum: 15-20%; Tungsten: 10-15%; Nickel: 14-20%; Iron: 3-8%; Molybdenum: 9-13%; The balance is one or more of ruthenium, platinum, zirconium and boron; The grain size of the high entropy alloy coating is ≤1 μm and the density is ≥99.8%.
2. A high entropy alloy coating according to claim 1, characterized in that: The thickness is 0.1-0.6 μm; and / or the surface roughness is less than 0.5 μm.
3. The high entropy alloy coating according to any one of claims 1 to 2, characterized in that: Thermal conductivity ≥140W / (m·K).
4. A nickel-based interface cone with a high entropy alloy coating as claimed in any one of claims 1 to 3.
5. The nickel-based interface cone with high entropy alloy coating according to claim 4, characterized in that: The continuous working time under 4000-8000K high temperature plasma bombardment is ≥80h.
6. The nickel-based interface cone with a high entropy alloy coating according to claim 4, characterized in that: In a working environment of pH ≤ 3 or pH ≥ 9, no corrosion products will fall off, and the amount of impurities introduced is ≤ 0.5ppm.
7. A method for preparing a nickel-based interface cone with a high entropy alloy coating according to claims 4-6, characterized in that: The following steps are involved: S1, sputtering coating: in an inert gas atmosphere, using the high entropy alloy as a target, a high entropy alloy coating is prepared on the surface of a nickel-based interface cone by magnetron sputtering; S2, coating heat treatment: subjecting the nickel-based interface cone with a high entropy alloy coating sputtered on its surface to vacuum heat treatment, followed by cooling to obtain the nickel-based interface cone with a high entropy alloy coating.
8. The method for preparing a nickel-based interface cone with a high entropy alloy coating according to claim 7, characterized in that: Step S1: The inert gas is argon, and the pressure of the argon atmosphere is (2-5)×10 -1 Pa; and / or, the power of the magnetron sputtering is 50-80W and the time is 5-10min; and / or, the magnetron sputtering power supply adopts a DC power supply.
9. The method for preparing a nickel-based interface cone with a high entropy alloy coating according to claim 8, characterized in that: Step S2: The vacuum degree of the vacuum heat treatment is ≤2×10 -4 Pa, the holding temperature is 300-500℃, and the holding time is 0.5-3h.
10. The method for preparing a nickel-based interface cone with a high entropy alloy coating according to claim 7, characterized in that: Before step S1 sputtering coating, the following steps are also included: S0 pre-sputtering: using a baffle to cover the nickel-based interface cone, pre-sputtering the target material, and removing the target material stress and surface oxide layer.
11. The method for preparing a nickel-based interface cone with a high entropy alloy coating according to claim 10, characterized in that: The pre-sputtering in step S0 is carried out at a pressure of (1-3)×10 -1 The pre-sputtering is carried out in an argon atmosphere of 0.06 Pa, and / or the pre-sputtering power is 30-150 W, and the pre-sputtering time is 3-15 min.
12. The method for preparing a nickel-based interface cone with a high entropy alloy coating according to any one of claims 7 to 11, characterized in that: Before sputtering coating, the method further includes: using an acidic washing solution with a mass ratio of hydrochloric acid to sulfuric acid of 1:(0.8-1.2) and a total mass concentration of ≤10% to soak and clean the nickel-based interface cone, wherein the soaking and cleaning time is 5-15 minutes, and the surface roughness of the nickel-based interface cone after soaking and cleaning is 1-5μm; and / or, before sputtering coating, the method further includes: heating the nickel-based interface cone to 100-250°C and keeping it warm for 5-15 minutes.
Citation Information
Patent Citations
Thermal protection element made of a quasicrystalline aluminum alloy
CA2106399A1
Amorphous high-entropy alloy thick film preparation equipment and preparation method
CN114921757A
Snow melting system
KR102280829B1
Method of forming a diffusion bonded joint
US20200290314A1
Composite material having high thermal conductivity and process of fabricating same
WO2011049479A1
Cited By
Pneumatic devices including surface coatings
US20260193747A1